Acting Responsibly in Nepal: Some Anthropological Remarks on Women’s Experience of Pelvic Organ Prolapse - Dahal, Kapil B. (Molung Educational Frontier, 2024)
Often, it is taken for granted that individual ‘act responsibly’ in their health-related behaviour. However, while minutely observing people’s behaviours and practices that directly and indirectly affect their health and well-being, it appears that such seemingly inherent ideas and practices do not always remain valid, and we can see individuals performing at par below rationality. In this article, I examine whether this notion is an innate quality of human beings and intrinsic to individuals or is it a socially constructed phenomenon? If so, this paper interrogates and highlights, in what kinds of cultural and social contexts individuals cannot act responsibly in a way that eventually promotes their health and well-being or reduces their vulnerability to problematic health situations. This paper is based on some ethnographic information generated through multiple research studies conducted in different periods in Nepal, aiming to understand women’s lived experiences of and the health care provisions regarding uterine prolapsed in Nepal. Various forms of interactions and observations techniques were employed to generate information for these studies. Thematic analysis has been employed in the process of navigating through the qualitative information acquired through these studies.